A stable π-conjugated singlet biradical - Hinkel, Felix Peter; Freudenberg, Jan; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2016)
A large polycyclic hydrocarbon with a singlet biradical ground state has been obtained by the combined effects of topology and electron-accepting aromatic substituents, which stabilize its open-shell singlet state.
Gesehen am 14.05.2020